MODERN TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE (AI) IN ENGLISH LANGUAGE TEACHING - Nabieva Gulbakhor Botirali kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article explores the integration of modern technologies and Artificial Intelligence (AI) in English language teaching. It highlights how AI tools, digital platforms, and adaptive learning systems enhance language acquisition, learner engagement, and personalized instruction. The study examines practical applications, challenges, and future prospects of using AI to support educators and students in developing effective communication skills.